Malignes Melanom - Winkler, Julia K.; Buder-Bakhaya, Kristina; Dimitrakopoulou-Strauss, Antonia; Enk, Alexander; Hassel, Jessica C. (Der Radiologe, 2017)
Clinical issueThe incidence of malignant melanoma is continuously increasing. The prognosis of metastatic disease is still limited.Standard treatmentUntil a few years ago palliative chemotherapy with a limited response rate was the standard treatment for metastatic melanoma.Treatment innovationsImmunotherapy and targeted therapy provide new treatment options. Immune checkpoint inhibitors have significantly improved the prognosis.Diagnostic work-upRegional lymph node sonography, computed tomography (CT) of the neck, chest and abdomen and brain magnetic resonance imaging (MRI) are routinely used. As an alternative to CT scans 18 F fluorodeoxyglucose positron emission tomography (FDG-PET) may be used.Performance and achievementsImmunotherapy provides the chance of long-term disease control in metastatic melanoma. Ipilimumab may provide long-term tumor control in approximately 20% of patients. Median overall survival of approximately 2 years is achieved during therapy with anti-programmed cell death (PD) 1 antibodies. For combined therapy of ipilimumab and nivolumab a response rate of almost 60% is achieved and 2‑year survival is also approximately 60%. The range of immune-mediated side effects demands particular consideration. For response evaluation immune-related response criteria were defined. Furthermore, immunotherapeutic approaches, such as talimogene laherparepvec (T-VEC), which is a modified herpes virus can be used for intralesional injection.Practical recommendationsAn individual definition of the appropriate therapy for each patient is of particular importance. In the context of modern therapy regimens close patient monitoring is crucial.